2018
DOI: 10.1021/acsami.8b06664
|View full text |Cite
|
Sign up to set email alerts
|

Diphenylethylenediamine-Based Potent Anionophores: Transmembrane Chloride Ion Transport and Apoptosis Inducing Activities

Abstract: Synthetic anion transporters have been recognized as one of the potential therapeutic agents for the treatment of diseases including cystic fibrosis, myotonia, and epilepsy that originate due to the malfunctioning of natural Cl ion transport systems. Recent studies showed that the synthetic Cl ion transporters can also disrupt cellular ion-homeostasis and induce apoptosis in cancer cell lines, leading to a revived attention for synthetic Cl ion transporters. Herein, we report the development of conformationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 68 publications
1
50
0
Order By: Relevance
“…LUVs were prepared following a standard literature method. 66 20 mM DOPC/DOPG -LUVs containing 100 mM NaCl in the intravesicular and 100 mM NaNO 3 in the extravesicular space were prepared by mixing DOPC and DOPG in molar ratio of 7 : 3 from chloroform stocks in a clean and dry round bottom flask. A thin film of DOPC/DOPG was obtained by purging nitrogen gas for 30 min over the chloroform solution.…”
Section: Preparation Of Large Unilamellar Vesicles (Luvs) Of Dopc : Dopgmentioning
confidence: 99%
See 1 more Smart Citation
“…LUVs were prepared following a standard literature method. 66 20 mM DOPC/DOPG -LUVs containing 100 mM NaCl in the intravesicular and 100 mM NaNO 3 in the extravesicular space were prepared by mixing DOPC and DOPG in molar ratio of 7 : 3 from chloroform stocks in a clean and dry round bottom flask. A thin film of DOPC/DOPG was obtained by purging nitrogen gas for 30 min over the chloroform solution.…”
Section: Preparation Of Large Unilamellar Vesicles (Luvs) Of Dopc : Dopgmentioning
confidence: 99%
“…68,69 The experimental setup was further validated by a selective anionophore prodigiosine (Fig. S12 †), 66 and a membrane disrupting agent Triton-X (Fig. S13 †).…”
Section: Nmr Measurementsmentioning
confidence: 99%
“…These molecules carried anions with significant transport efficiency versus other biologically relevant cations and the antiport mechanism could be identified (Figure 12D). [47] Here, anion carriers induced perturbation of Cl À ion homeostasis and led to the death of HeLa cell line by promoting the caspase-mediated intrinsic pathway of apoptosis. Last year, Rawling et al reported a series of fatty acid substituted urea-based (also termed as, aryl-urea) anion transporters (45 a-45 d) and their function as mitochondrial uncouplers.…”
Section: Acyclic Anionophores Based On Urea and Thioureamentioning
confidence: 99%
“…A literature search shows that egg yolk phosphatidylcholine (EYPC) and 2-oleoyl-1-palmitoyl-sn-glycero-3phosphocholine (POPC, Figure 5) are the most commonly used lipids; however, 1palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2oleoyl-sn-glycero-3-phosphoglycerol (POPG) have also been employed. For instance, Matile's, [22][23][24][25][26][27] Talukdar's, [28][29][30][31][32] and Ballester's 22,33 research groups have used EYPC from Avanti Polar Lipids, while Chen [34][35][36][37][38] and Manna 39,40 have also used EYPC but purchased from Sigma-Aldrich. On the other hand, the Gale, 15,18,21,[41][42][43][44] and Quesada 45, As indicated before, when it comes to choosing the appropriate lipid to conduct transport assays, the decision should be made by considering, among other factors, the biological membranes to be mimicked.…”
Section: Lipidsmentioning
confidence: 99%
“…16,21 Finally, it is important to note that sometimes a mixture of lipid and cholesterol has been prepared to carry out transport experiments due to the contribution of the latter to the stabilisation of the vesicles' membrane. 34,39,40,46 Their proportions may vary, but Quesada's group uses a 7:3 POPC:cholesterol mixture with good results.…”
Section: Lipidsmentioning
confidence: 99%